Soccer injury prevention and treatment a guide to optimal performance for players, parents and coaches - Gallucci, John, Jr (Demos Medical, 2014)
Soccer has a higher injury rate than any other contact sport. Student athletes, weekend warriors, and professional players alike all need guidance to prevent the injuries that can put you out of the game. Soccer Injury Prevention and Treatment is your comprehensive, illustrated guide to the best training, strengthening, stretching, nutrition, and hydration regimes to keep you safe and on the field. John Gallucci, physical therapist and medical coordinator for Major League Soccer, helps you understand common injuries so you can play smarter and heal better when injuries do occur. Included are treatments for specific injuries like shin splints, ACL tears, and concussions, as well as guidelines specifically for young players.